The Effects of Renewable Energy Sources on the Trade Balance in Türkiye - Çam, Savaş; Aktaş, Erkan (Journal of Applied And Theoretical Social Sciences, 2024)
Introduction: Having domestically producible energy resources is a crucial factor for sustainable economic growth and development. Countries lacking these resources and depending heavily on energy imports can experience significant imbalances in their trade balances. Energy imports also constitute one of the largest components of the current account deficit. An increase in the current account deficit is a significant factor contributing to economic crises in such countries. In countries without sufficient fossil fuel resources, energy imports are among the primary causes of trade deficits. This study examines the impacts of Turkey’s renewable energy-based production on its trade balance. Method: A time series analysis was conducted using data on renewable energy production and trade balance. The period from 1991 to 2022 was analyzed using the Autoregressive Distributed Lag (ARDL) bounds testing approach. Results or Findings: The analysis of the relationship between the trade balance and the utilization of renewable energy resources indicates a statistically significant and long-term negative relationship between these two variables. Discussion or Conclusion: In light of these results, the presence of a statistically significant and negative correlation between renewable energy production and trade balance in Turkey over the long term highlights renewable energy as a crucial factor for sustainable economic growth.